Job satisfaction and turnover intention of preventive medicine workers in northern Vietnam: Is there any relationship? - Quynh Anh Nguyen; Anh Dung Tran (Health Services Insights, 2021)
To access the relationship between job satisfaction and turnover intention of preventive medicine workers in Vietnam, we conducted a cross-sectional study using a purposive convenience sample of 12 preventive medicine centers in 3 provinces of northern Vietnam (Hai Duong, a plain province, Yen Bai, a mountainous province, and Hanoi, the capital of Vietnam). Overall, 400 preventive medicine staff were invited to participate, and 383 questionnaires were analyzed (153 from 3 provincial centers and 230 from 9 district centers). All eligible participants completed the questionnaire, which included questions relating to general information, job satisfaction, intention to quit. We identified significant associations between turnover intention and personal factors, including age, marital status, education level, professional degree, and length of employment at the current center. The bivariate analysis also indicated that job satisfaction had an inverse relationship with turnover intention, as expected. The correlations varied between facets and overall job satisfaction, from −0.19 for community support to −0.37 for overall job satisfaction. These correlations remained significant after controlling for personal factors using hierarchical multiple regressions. The results indicated that facet and overall job satisfaction were significant predictors of turnover intention, while overall job satisfaction was the strongest predictor (β = 0.37, P  < .001). This study could contribute to local system development and the international understanding of job satisfaction and turnover intention among preventive medicine workers. Addressing the aspects of job satisfaction that were found to have the lowest scores may help the preventive medicine system to retain staff.